The Needs for Septage Treatment Plant in The Urban Areas of Blitar Regency: A Research Study - Pratiwi, Yeni; Purwanti, Ipung Fitri; Hermana, Joni (IPTEK The Journal for Technology and Science, 2020)
Blitar is one of the regencies in Indonesia that doesn’t have Septage Treatment Plant (STP). The high coverage of on-site wastewater system access as well as routine desludging needs in the Decentralized Wastewater Treatment Plant (DWWTP) requires further septage process of septage in the form of STP. However, almost 90% of STP in Indonesia was not working correctly due to poor effluent quality and inadequate operational and maintenance costs. This study referred to the current conditions of domestic wastewater management obtained from interviews and questionnaires to identify the real needs of establishing STP efficiently and sustainably. Furthermore, this paper contained the analysis of STP capacity, site selection, sludge treatment units, land requirements, capital costs, operational and maintenance costs. By considering the existing desludging activity, the capacity of STP in 2019 was 20.95 m3/day. Meanwhile, the capacity of STP at the end of the 20-year design period was 41.36 m3/day. Although site selection analysis was obtained three locations for STP, the selected location of STP was the one which was centrally located in one location, namely Sutojayan Sub-District. One location of STP was considered to be more efficient from land needs, capital cost, operational and maintenance costs. The total land requirement of the STP was 2,196.49 m2. The capital cost amounted to IDR 15,562,028,000. The operational and maintenance costs were IDR 319,715/day, while the underlying service tariff charged to the community was IDR 188,000/septic tank.